THE UTILIZATION OF DIGITAL INFLUENCERS AS A PROMOTION STRATEGY FOR THE KAYUTANGAN HERITAGE AREA OF MALANG CITY - Yulistiowati, Irma Mufita; Aditya, Feriz Rizki; Effendy, Rochmad (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
Kayutangan Heritage in Malang City is one of the historical tourist destinations that has great potential to attract tourists, especially millennials and Gen Z who are active on social media. This paper aims to provide a strategy scheme for the manager of Kayutangan Heritage tourist area, to be more active in utilizing the role of digital influencers as part of the strategy to attract tourists, based on the content they share on social media. The purpose of this study is to analyze strategies in establishing relationships with digital influencers in the Kayutangan Heritage area. Using a qualitative approach, this research involved in-depth interviews with influencers, area managers, and tourism industry experts. The results showed that collaboration with digital influencers can increase visibility and build a positive image of the area through creative content that is authentic and relevant to the target audience. The research also revealed that an effective relationship with influencers requires open communication, a deep understanding of each party's values and characteristics, and a clear agreement on goals and expectations. By establishing strong and sustainable relationships, Kayutangan Heritage area can strengthen its appeal and achieve broader promotional goals in today's digital era.